Neural Mechanisms of Cognitive Behavioral Therapy Efficacy in Anxiety Disorders: A Scoping Review of fMRI-Based Studies That Tested the Dual Model - Judith Domínguez-Pérez; Wenceslao Peñate-Castro; Francisco Luis Rivero-Pérez (Life)
Anxiety disorders are common mental health conditions characterized by excessive fear and anxiety. Cognitive behavioral therapy (CBT) has demonstrated efficacy, yet the possible neurobiological mechanisms underpinning its effects remain debated. The dual-route model offers a potential explanation by suggesting that CBT increases activation in the brain areas responsible for emotion regulation while decreasing activation in limbic areas. This scoping review examined possible neurobiological mechanisms supporting CBT’s efficacy in anxiety disorders by exclusively reviewing studies that utilized functional magnetic resonance imaging (fMRI). The included studies published since 2018 focused on adult samples that received CBT for anxiety disorders, with pre- or post-treatment fMRI data. The data extraction followed a standardized process, with key variables, such as the study design, population, and neuroimaging findings, systematically charted. While the dual-route model explains key aspects of CBT’s neurobiological effects, the findings suggest the need for expansion to incorporate areas such as the precuneus, particularly in specific phobias and social anxiety disorder. Further research is required to refine this model and explore additional mechanisms underlying CBT’s efficacy.